Eye in the sky [videorecording (DVD)] - Mirren, Helen; Paul, Aaron, 1979-; Rickman, Alan (Universal Studios ; Universal Pictures Home Entertainment, 2016)
Col. Katherine Powell, a military officer in command of an operation to capture terrorists in Kenya, sees her mission escalate when a girl enters the kill zone, triggering an international dispute over the implications of modern warfare.